Using Riddles Technique to Develop Students’ Vocabulary Mastery - Trisnawati, Trisnawati; Mertosono, Sudarkam; Jamiluddin , Jamiluddin; Maf’ulah, Maf’ulah (Universitas Cokroaminoto Palopo, 2023)
The educational value of applying the riddles technique is to develop students’ vocabulary mastery at SMP Negeri 1 Sausu. Students’ lack of vocabulary, especially about countable nouns and students’ participation throughout the procedure of instruction in the class are the reasons for carrying out this research. The researchers applied a quasi-experimental research design, includes experimental and control class. In the academic year 2022-2023, students in first grade at SMP Negeri 1 Sausu made up the population, includes the classes VIIA and VIIB. The total number of students were 77 students. The sample class was determined using a cluster sampling technique. The instrument in this research was tests, pre-test and post-test. The researchers come to the conclusion that using riddles technique can develop students’ vocabulary mastery in the first grade of SMP Negeri 1 Sausu. It was evidenced by the experimental class’s post-test results (79.29), that was higher than the control class’s post-test (68.40). Also, the t-counted score (8.52) was exceeds than the t-table value (1.674).